Caracterización productiva de la postura en reproductoras Cobb-500, durante el periodo, inicio y pico de postura en San Pedro de Lloc - Bacilio Garcia, Herry Diego (2019)
The present work evaluated the production of cobb 500 breeding hens of the company "Don pollo S.A.C", from September 2018 to November 2018. We worked with a lot of 377 birds housed in the farm Chilco located in the province of Pacasmayo. The start and peak of the production were evaluated for a period of 09 weeks (24 to 32 weeks of age) in order to verify the characterization in the productive and economic behavior of the production of eggs for chicken’s BB parrilleros. The results were subjected to an analysis of variance and comparison of means and proportions. A viability of 95% was determined in the production phase of heavy reproductive hens exploited in the District of San Pedro de Lloc; in the same order, a mortality of 1.86% was observed. The average consumption per day / bird was 155 g, totaling 9.29 kg per period in the breeders. Egg production per batch at its maximum peak was 313 units (84.45% laying) The proportion of API eggs produced (98.4%) determined a total of 12761.56 eggs. The productive results achieved in heavy breeders obtained a lower productive performance than the indices established for the 500 cobb line. Finally, it is concluded that the productive indices achieved were well approved by the company's management.